Establishing Bio-bank in Nepal - Tamang, Man Kumar; Yadav, Uday Narayan (Journal of Nepal Health Research Council, 2020)
Globally, the establishment of bio-banks began around 1990s when scientists felt need for collaborative researches in biomedical field. Bio-banks collect and preserve biological specimens which are provided to researchers to investigate about specific disease or treatment. In Nepal, eye bank and skin bank are only two types of bio-banks currently in existence. However, specimens collected in these bio-banks are used only for medical treatment, not for research. With this regard, there is urgent need to establish bio-banks in Nepal. In this article, we aim to provide insights on current status of bio-banking and its benefits for scientific development of Nepal. Keywords: Bio-bank; eye bank; Nepal; skin bank